Economic Cooperation as a Factor in the Development of Modern Enterprise - Guzdek, Sylwia (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2016)
Economic cooperation is a multifaceted concept that is difficult to classify. Numerous scientific studies have confirmed the complexity of organisational relationships and the forms they take. This short paper examines the benefits and risks of economic cooperation and, using a review of the literature, discusses the theoretical essence of economic cooperation, the forms it takes and the importance it carries for the entities cooperating. It is hypothesised that economic cooperation is one of the main conditions modern enterprises must engage if they wish to develop.